1974
DOI: 10.1530/jrf.0.0390053
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Development in the Infant Human Ovary

Abstract: The morphology and growth pattern of human ovarian follicles has been studied between birth and 9 years of age. Follicles have been classified according to their morphology, diameter, the diameter of the oocyte and the number of granulosa cells in the widest cross-section. Nine major classes offollicle were recognized. The smallest, Class B follicles, contained a non-growing oocyte and were surrounded by a single layer of flattened granulosa cells. The largest, Class F follicles, which were up to 6 mm in diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
63
0
1

Year Published

1974
1974
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 28 publications
7
63
0
1
Order By: Relevance
“…primordial, primary and secondary), was smaller than those observed in ewes (Lundy et al, 1999) and cows (Van Wezel and Rodgers, 1996, Braw-Tal and Yossefi, 1997, but was similar to those observed in humans (Lintern-Moore et al, 1974). However, the mean and range in the number of granulosa cells at the equatorial section were compatible to those described for ewes (Lundy et al, 1999), cows (Braw-Tal and Yossefi, 1997) and humans (Lintern-Moore et al, 1974), even when the diameter of oocytes and follicles was smaller. These differences may be species-specific or due to differences in measurement techniques.…”
Section: Discussionsupporting
confidence: 79%
“…primordial, primary and secondary), was smaller than those observed in ewes (Lundy et al, 1999) and cows (Van Wezel and Rodgers, 1996, Braw-Tal and Yossefi, 1997, but was similar to those observed in humans (Lintern-Moore et al, 1974). However, the mean and range in the number of granulosa cells at the equatorial section were compatible to those described for ewes (Lundy et al, 1999), cows (Braw-Tal and Yossefi, 1997) and humans (Lintern-Moore et al, 1974), even when the diameter of oocytes and follicles was smaller. These differences may be species-specific or due to differences in measurement techniques.…”
Section: Discussionsupporting
confidence: 79%
“…The results showed that the mean diameter of zebu oocytes and follicles and the mean number of granulosa cells at the equatorial section were similar to those observed for European cattle (Van Wezel and Rodgers, 1996, Braw-Tal and Yossefi, 1997and Hyttel et al, 1997 in all three developmental stages evaluated (i.e., primordial, primary and small secondary follicles). Also, our results were similar to those described for humans (Lintern-Moore et al, 1974), but different from those described for ewes (Lundy et al, 1999) and goats (Lucci et al, 2001). …”
Section: Discussionsupporting
confidence: 68%
“…primordial, primary and secondary). Also, our results were similar to those described for humans [39], but different from those described for ewes [40] and goats [41]. In addition, some polyovular follicles could be observed in Zebu cow ovaries.…”
Section: Discussionsupporting
confidence: 67%